Media literacy and mental health awareness: A quantitative study of Bangladeshi university students - Haque, Md. Shahidul; Shafiuzzaman, Md. (Jurnal Komunikasi, 2026)
This study investigates the relationship between media literacy and mental health awareness among university students in Bangladesh. A quantitative cross-sectional study was conducted among 120 university students of four public universities in Bangladesh. The data has been collected using a structured format of a questionnaire that measures media consumption behaviors, literacy skills, and mental health awareness levels of participants. The findings indicate that students with stronger media literacy skills demonstrate a greater ability to recognize inaccurate information, critically interpret media representations of mental health, and develop more informed attitudes toward mental health issues. The results also reveal a positive association between media literacy competencies and students’ awareness of mental health problems as well as their acceptance of non- stigmatizing portrayals of mental illness in media content. In addition, the study highlights that although students frequently engage with digital media platforms, their ability to critically evaluate mental health portrayals in media varies depending on their level of media literacy. These findings contribute to existing literature by providing empirical evidence from the Bangladeshi context, where research examining the relationship between media literacy and mental health awareness remains limited.